2000
DOI: 10.1046/j.1440-1746.2000.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastroallergic anisakiasis: Findings in 22 patients

Abstract: Anisakis simplex parasitism was the causative agent of allergic and gastric symptoms. Gastroallergic anisakiasis appears to be a relatively common disease, that may have been underdiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 9 publications
0
31
0
4
Order By: Relevance
“…Allergies to L3 infection have previously been diagnosed by positive skin prick tests, specific IgE production, and total elevation of IgE levels Moreno-Ancillo et al, 1997;Lopez-Serrano et al, 2000;Moneo et al, 2000;Purello-D'Ambrosio et al, 2000). Daschner et al (2002) has elucidated in detail the time course of IgE production in human L3-dependent allergies.…”
Section: Specific Immunoglobulin E Production and Allergy To L3mentioning
confidence: 99%
“…Allergies to L3 infection have previously been diagnosed by positive skin prick tests, specific IgE production, and total elevation of IgE levels Moreno-Ancillo et al, 1997;Lopez-Serrano et al, 2000;Moneo et al, 2000;Purello-D'Ambrosio et al, 2000). Daschner et al (2002) has elucidated in detail the time course of IgE production in human L3-dependent allergies.…”
Section: Specific Immunoglobulin E Production and Allergy To L3mentioning
confidence: 99%
“…Nowadays, however, health authorities and the fishing industry are increasingly becoming aware of the problems caused by these parasites, which affect both human health and the commercial value of the product. Species of the family Anisakidae have acquired importance due to the traumatic effect produced by the third larval stage when it becomes attached to the wall of the human digestive tract (Ooiwa et al 1989, Kikuchi et al 1990, Ishikura et al 1992, Louredo Méndez et al 1997 and to allergic episodes caused by their metabolic antigens following ingestion of the parasitized fish (Mendizábal-Basagoiti 1999, López-Serrano et al 2000, Foti et al 2002. Over the last decade a number of cases of anisakidosis in man have been reported in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Daschner et al reported a case of a 66-yearold man with severe epigastric pain and urticaria; a total of 20 larvae were removed using upper endoscopy (10). The other previously reported cases also had multiple Anisakis larvae that were endoscopically removed (11,12).…”
Section: Discussionmentioning
confidence: 88%